Cemaran Bakteri pada Makanan Pempek Produksi Rumah Tangga dan Pabrik Pengolah Makanan - Joko Sapto Pramono; Mustaming Mustaming; Dewi Samara Putri (Poltekkes Kemenkes Kendari, 2020)
Pempek is a traditional Palembang dish. The food is processed by home and food processing industries. The bacteria Escherichia coli, Salmonella, and Staphylococcus aureus are at risk for infection of these processed fish. The purpose of this research is to determine the bacterial contamination of products sold on the public market of Samarinda. This type of study was descriptive analysis with a cross-sectional design. Random sampling is the sampling method used. 20 samples were collected, 10 homemade manufacturing samples, and 10 factory manufacturing samples. The samples are then taken to the laboratory and a colony counter is used to monitor the number of colonies. The outcome of the Total Plate Count measurement on Plate Count Agar (PCA) media has demonstrated that 18 samples (90%) consisting of 10 samples of factory-produced performance and 8 homemade performance samples contain high contamination microbial levels (> 5x104). Pempek should be cooked until it is fully mature to avoid the possibility of infection by pathogenic bacteria before eating both factory-produced and homemade products.